BAKTI: Batik Khas Tangan Indonesia Support Class V Mulok Batik Learning - Triyono Triyono; Achmad Buchori (Universitas PGRI Semarang, 2024)
The world of education has a very important role in the development of learning, especially for students. Learning in the independent curriculum emphasizes learning strategies that utilize local wisdom and cultural uniqueness in the region. Until now, several innovations have been discovered in the formation of batik motifs. Based on the above phenomenon, entrepreneurship education needs to be carried out from an early age with children, especially in the school environment. The method in this research is that students are trained to make stamped batik at a batik museum. Practices at the batik museum include preparing the materials from the start, then preparing and also the final or finishing process. The next stage is that students begin to implement the training carried out. Students and teachers prepare the tools and materials needed. The results of this research are children's enthusiasm for selling BAKTI batik through events at school, whether at work exhibitions, book exhibitions or festivals held outside the school.